A wave of protectionism? An analysis of economic and political considerations - Philipp Maier (Bank of Canada, 2008)
In light of the U.S. current account deficit, pressure is high on Asian countries to revalue their currencies. The calls from some U.S. policymakers for tariffs on imports from China has sparked fears that this could trigger a world-wide surge in protectionism. This study evaluates the risk of protectionism, considering two dimensions: first, the economic effects of tariffs; second, the incentives for policymakers to adopt tariffs. Following the political economy literature, we distinguish benevolent policymakers who care about long-term GDP and myopic policymakers, for whom short-term considerations are important. An analysis of the economic effects using the Bank of Canada's Global Economy Model shows that the gains from import tariffs are small: in the short-term, tariffs raise the price of imports and shift consumption toward domestically-produced goods; but they also lead to a real appreciation. This improves the terms of trade, but falling export volumes lead to a reduction in GDP in the long-run. As regards the political dimension, we conclude that a benevolent policymaker would not adopt tariffs, because of negative long-term economic consequences, but myopic policymakers might be tempted to exploit short-term political gains. Given the potentially high costs of protectionist trade policies, protectionism is therefore rightly viewed as an important risk.
Keywords: E66; F32; F47; 330; International topics; Recent economic and financial developments; Regional economic developments; Internationale Wirtschaftsbeziehungen; Protektionismus; Außenhandelsbeschränkung; Wechselkurs; Terms of Trade; Wohlfahrtseffekt; Kanada; Aufstrebende Märkte; USA